2016
DOI: 10.1037/cns0000055
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing sports performance with hypnosis: An ode for Tiger Woods.

Abstract: We present a comprehensive methodological review of controlled and single-case design studies of the effectiveness of hypnosis for enhancing sports performance. To be included in the review, controlled studies were required to use a between-subjects or mixed model design in which hypnosis was compared with a control condition or alternative intervention to improve sports performance. Single case-design studies were required to incorporate baseline and intervention phases, with multiple assessment points during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 53 publications
(150 reference statements)
1
8
0
Order By: Relevance
“…However, it is crucial to remember that each athlete has unique needs and psychological characteristics. Therefore, personalising the hypnosis approach according to each athlete's needs is imperative for its effectiveness (Milling & Randazzo, 2016). To this end, sport psychologists and coaches should collaborate on developing individualised programmes tailored to each athlete's unique psychological makeup.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is crucial to remember that each athlete has unique needs and psychological characteristics. Therefore, personalising the hypnosis approach according to each athlete's needs is imperative for its effectiveness (Milling & Randazzo, 2016). To this end, sport psychologists and coaches should collaborate on developing individualised programmes tailored to each athlete's unique psychological makeup.…”
Section: Resultsmentioning
confidence: 99%
“…In previous research related to hypnosis, the focus has been more inclined towards sports such as basketball, golf, football, tennis, and badminton (Dionigi et al, 2018;Milling & Randazzo, 2016). There is a lack of research specifically exploring the use of hypnosis in volleyball.…”
Section: Introductionmentioning
confidence: 99%
“…Hypnosis has been shown to be effective for improving performance in a variety of sports, with strongest support for its use in basketball, golf, soccer, and badminton (reviewed in Milling & Randazzo, 2016). Of note, Pates and colleagues have consistently demonstrated that a hypnosis intervention designed to increase flow state (sometimes called "being in the zone") was useful for enhancing performance in golf (Pates, 2013;Pates & Maynard, 2000;Pates, Oliver, & Maynard, 2001) and basketball (Pates et al, 2002;Pates, Maynard, & Westbury, 2001).…”
Section: Other Promising Applications Of Hypnosismentioning
confidence: 99%
“…Meanwhile, hypnosis is a simple and easy way to adjust the physical and mental conditioning without special requirements in terms of venues or equipment. A previous review indicated that hypnosis was effective for improving performance across multiple sports, with the strongest results found for basketball, golf, soccer and badminton ( Milling and Randazzo, 2016 ). Therefore, hypnosis is widely used in sports and competitions.…”
Section: Athletes’ Psychological Stressmentioning
confidence: 99%